1999
DOI: 10.1080/01919519908547261
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Removal of Biodegradable Ozonation By-Products during Ozonation-Biofiltration Treatment: Pilot-Scale Evaluation

Abstract: An ozonation-biological filtration pilot-scale study was performed to evaluate the formation and removal of biodegradable ozonation by-products. The formation of aldehydes and ketoacids was found to be proportional to the DOC concentration and ozone dosage, and a strong relationship between the formation of aldehydes, ketoacids, and biodegradable dissolved organic carbon (BDOC) was observed. Four types of granular activated carbon (GAC) and one nonadsorbing medium, biolite, were employed to evaluate the perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 18 publications
0
19
0
4
Order By: Relevance
“…Correlation between aldehydes and assimilable organic carbon (AOC) has been shown by Schechter and Singer (2). Griffini et al (12) have also observed a relationship between the biodegradable dissolved organic carbon and the sum of aldehydes and ketoacids. A correlation between AOC and ketoacids has been also reported (9)(10)(11).…”
Section: Introductionmentioning
confidence: 93%
“…Correlation between aldehydes and assimilable organic carbon (AOC) has been shown by Schechter and Singer (2). Griffini et al (12) have also observed a relationship between the biodegradable dissolved organic carbon and the sum of aldehydes and ketoacids. A correlation between AOC and ketoacids has been also reported (9)(10)(11).…”
Section: Introductionmentioning
confidence: 93%
“…Other major by-products identified in this study include three ketoacids (i.e., glyoxylic, pyruvic, and ketomalonic acids) and two carboxylic acids (i.e., formic and oxalic acids). These oxidation by-products are more biodegradable than their precursors, thus probably raising the risk of microbial regrowth in water distribution systems (Gagnon et al, 1997;Griffini et al, 1999;DiGiano et al, 2001). The yields of aldehydes and acetone after ozonation and catalytic ozonation of individual NOM fractions are summarized in Table 2.…”
Section: Oxidation By-productsmentioning
confidence: 99%
“…According to former researches (Gagnon et al, 1997;Griffini et al, 1999;DiGiano et al, 2001), all of these oxidation byproducts are readily biodegradable. Schechter and Singer (1995) showed a correlation between aldehydes and assimilable organic carbon (AOC).…”
Section: Oxidation By-productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dissolved natural organic matter (DOM) dominates in DOC before and after conventional water treatment processes. Moreover, DOM is the precursor of disinfection by-products (DBPs) and the nutrient for bacteria reproduction in water distribution systems (Singer, 1999;Griffini et al, 1999). Therefore, it is very important to investigate the impact of catalytic ozonation on DOM destruction in comparison to ozonation alone.…”
Section: Introductionmentioning
confidence: 99%